Tick species (Acari: Ixodidae and Argasidae) of Colombia - López Valencia, Gustavo (Revista Colombiana de Ciencias Pecuarias, 2017)
Ticks are external parasites that feed on blood and affect all vertebrate species. They can constitute a serious constraint to the economy of livestock enterprises, especially in the tropical regions of the world. Ticks, together with other invertebrates such as insects, spiders, mites and crustaceans belong to the phylum Arthropoda. Arachnids and insects are two major classes within the phylum. There are about 907 species of ticks described in the world, all grouped in the suborder Ixodida (Metastigmata). The Ixodida suborder is divided into three families: a) The Ixodidae family, which corresponds to ticks commonly known as hard ticks, with approximately 720 species described, b) The Argasidae family, known as soft ticks, with about 186 species, and c) The family Nuttaliellidae, with morphological characteristics intermediate between the former families and represented by a single species Nuttaliella namaqua which is restricted to the African continent and is found in the nests of swallows. The Ixodidae and Argasidae families are widely distributed across all continents and undoubtedly constitute the most important group among all ectoparasites that affect domestic and wild animals, and given the opportunity humans. Ticks are ectoparasites of great importance for public and animal health because they transmit pathogenic types of bacteria, viruses, protozoa, rickettsia, spirochetes and filarias. With heavy burdens, they also produce direct health effects, deteriorate skin quality, hinder the acclimatization of non-native breeds, produce mortality, and cause and overall decrease in animal production. In Colombia, 71 species have been identified; 52 Ixodidae of the following genus: Ixodes 17, Amblyomma 29, Dermacentor 1, Anocentor 1, Haemaphysalis 2 y Rhipicephalus 2, also 19 species of the family Argasidae (Argas 4, Ornithodoros 13, Otobius 1 y Antricola 1).